Intraoperative risk factors of acute kidney injury after liver transplantation. Issue 7 (25th April 2022) - Berkowitz, Rachel J.; Engoren, Milo C.; Mentz, Graciela; Sharma, Pratima; Kumar, Sathish S.; Davis, Ryan; Kheterpal, Sachin; Sonnenday, Christopher J.; Douville, Nicholas J.
Abstract: Acute kidney injury (AKI) is one of the most common complications of liver transplantation (LT). We examined the impact of intraoperative management on risk for AKI following LT. In this retrospective observational study, we linked data from the electronic health record with standardized transplant outcomes. Our primary outcome was stage 2 or 3 AKI as defined by Kidney Disease Improving Global Outcomes guidelines within the first 7 days of LT. We used logistic regression models to test the hypothesis that the addition of intraoperative variables, including inotropic/vasopressor administration, transfusion requirements, and hemodynamic markers improves our ability to predict AKI following LT. We also examined the impact of postoperative AKI on mortality. Of the 598 adult primary LT recipients included in our study, 43% (n = 255) were diagnosed with AKI within the first 7 postoperative days. Several preoperative and intraoperative variables including (1) electrolyte/acid‐base balance disorder (International Classification of Diseases, Ninth Revision codes 253.6 or 276.x and International Classification of Diseases, Tenth Revision codes E22.2 or E87.x, where x is any digit; adjusted odds ratio [aOR], 1.917, 95% confidence interval [CI], 1.280–2.869; p = 0.002); (2) preoperative anemia (aOR, 2.612; 95% CI, 1.405–4.854; p = 0.002); (3) low serum albumin (aOR, 0.576; 95% CI, 0.410–0.808; p = 0.001), increased potassium value during reperfusion (aOR, 1.513; 95% CI, 1.103–2.077; p = 0.01), and lactate during reperfusion (aOR, 1.081; 95% CI, 1.003–1.166; p = 0.04) were associated with posttransplant AKI. New dialysis requirement within the first 7 days postoperatively predicted the posttransplant mortality. Our study identified significant association between several potentially modifiable variables with posttransplant AKI. The addition of intraoperative data did not improve overall model discrimination.